Auditory and Visual Sensations - Ando, Yoichi (Springer New York : Imprint: Springer, 2010)
Professor Yoichi Ando, acoustic architectural designer of the Kirishima International Concert Hall in Japan, presents a comprehensive rational-scientific approach to designing performance spaces. His theory is based on systematic psychoacoustical observations of spatial hearing and listener preferences, whose neuronal correlates are observed in the neurophysiology of the human brain. A correlation-based model of neuronal signal processing in the central auditory system is proposed in which temporal sensations (pitch, timbre, loudness, duration) are represented by an internal autocorrelation representation, and spatial sensations (sound location, size, diffuseness related to envelopment) are represented by an internal interaural crosscorrelation function. Together these two internal central auditory representations account for the basic auditory qualities that are relevant for listening to music and speech in indoor performance spaces. Observed psychological and neurophysiological commonalities between auditory and visual sensations and preference patterns are presented and discussed. This book thus spans the disciplines of physics, acoustics, psychology, neurophysiology, and music production, thereby blending science, engineering, and art.